A question-answering system for Portuguese juridical documents - Quaresma, Paulo (2012)
We present a Question-Answering (QA) system for Por- tuguese juridical documents. The QA system was applied to the complete set of deci- sions from several Portuguese juridical institutions (Supreme Courts, High Court, Courts, and Attorney-General’s Office) in a total of 180,000 documents.